Розв’язання задач динаміки і стійкості дискретно-неперервних стрижневих систем - Тацій, Р. М.; Давидчак, О. Р. (Видавництво Національного університету «Львівська політехніка», 2006)
Запропоновано методику дослідження динаміки і стійкості стрижневих систем із довільним розподілом масами, жорсткості та навантаження, розроблену на основі алгоритму методу граничних елементів і методу дискретизації елементів. To find frequencies and forms of characteristic oscillations, critical (buckling) loads of durability of framed structures with discrete–continuous distribution of parameters, the presented article suggests using the boundary elements method with evolutionary operators that correspond to quasi–differential equations obtained during certain approximation of coefficients of corresponding equations.